Pre- and post-treatment of α-Tocopherol on cognitive, synaptic plasticity, and mitochondrial disorders of the hippocampus in icv-streptozotocin-induced sporadic Alzheimer’s-like disease in male Wistar rat - Nabavi Zadeh, Fatemeh; Nazari, Maryam; Amini, Abdollah; Adeli, Soheila; Barzegar Behrooz, Amir; Fahanik Babaei, Javad (Frontiers in Neuroscience, 2023)
Objective Most dementia cases in the elderly are caused by Alzheimer’s disease (AD), a complex, progressive neurological disease. Intracerebroventricular (ICV) administration of streptozotocin (STZ) in rat’s results in aberrant brain insulin signaling, oxidative stress, and mitochondrial dysfunction that impair cognition change neural plasticity, and eventually lead to neuronal death. The current study aims to define the neuroprotective action of alpha-tocopherol in enhancing mitochondrial function and the function of synapses in memory-impaired rats brought on by icv-STZ. Methods Male Wistar rats were pre-treated with (α-Tocopherol 150 mg/kg) orally once daily for 7 days before and 14 days after being bilaterally injected with icv-STZ (3 mg/kg), while sham group rats received the same volume of STZ solvent. After 2 weeks of icv-STZ infusion, rats were tested for cognitive performance using a behaviors test and then were prepared electrophysiology recordings or sacrificed for biochemical and histopathological assays. Results The cognitive impairment was significantly minimized in the behavioral paradigms for those who had taken α-Tocopherol. In the hippocampus of icv-STZ rat brains, α-Tocopherol ocopherol effectively prevented the loss of glutathione levels and superoxide dismutase enzyme activity, lowered mitochondrial ROS and mitochondrial membrane potential, and also brought about a decrease in Aβ aggregation and neuronal death. Conclusion Our findings demonstrated that by lowering neurobehavioral impairments caused by icv-STZ, oxidative stress, and mitochondrial dysfunction, α-Tocopherol enhanced intracellular calcium homeostasis and corrected neurodegenerative defects in the brain. These findings examine the available approach for delaying AD connected to mitochondrial malfunction and plasticity issues.